Genetic architecture and genomic prediction of cooking time in common bean (Phaseolus vulgaris L.) - Díaz, Santiago; Ariza-Suárez, Daniel; Ramdeen, Raisa; Aparicio Arce, Johan Steven; Arunachalam, Nirmala; Hernández Lira, Juan Carlos; Diaz, Harold; Ruíz Guzman, Henry Alonso; Piepho, Hans-Peter; Raatz, Bodo (International Center for Tropical Agriculture, 2020)
These datasets contain phenotypic and genotypic data of a MAGIC population, DOR364 x G19833 biparental population, VEF panel and MIP panel. The main goal for these populations is to be used for genetic analysis and applications in breeding and breeding tool development, as well as information for basic research questions aiming to uncover the genetic basis of seed quality traits. The raw phenotypic data come from trials carried out in Palmira (Colombia). The trials were laid out in the field with an alpha-lattice experimental design in 2011, 2013, 2017 and 2019. Three trails were assessed: Cooking time (CKT), Water absorption capacity (WAC) and seed weight (SdW). The agronomic performance of the population was modeled using linear mixed models. From these models, best linear unbiased predictors were obtained (BLUPs). The genotypic datasets include a variant call format (VCF) file from MAGIC population, VEF panel and MIP panel.